Pain and Body Awareness: Evidence from Brain-Damaged Patients with Delusional Body Ownership - Pia, Lorenzo; Garbarini, Francesca; Fossataro, Carlotta; Fornia, Luca; Berti, Anna M. (Frontiers in Human Neuroscience, 2013)
A crucial aspect for the cognitive neuroscience of pain is the interplay between pain perception and body awareness. Here we report a novel neuropsychological condition in which right brain-damaged patients displayed a selective monothematic delusion of body ownership. Specifically, when both their own and the co-experimenter’s left arms were present, these patients claimed that the latter belonged to them. We reasoned that this was an ideal condition to examine whether pain perception can be ‘referred’ to an alien arm subjectively experienced as one’s own. Seventeen patients (eleven with, six without the delusion), and ten healthy controls were administered a nociceptive stimulation protocol to assess pain perception. In the OWN condition, participants placed their arms on a table in front of them. In the ALIEN condition, the co-experimenter’s left (or right) arm was placed alongside the participants’ left (or right) arm, respectively. In the OWN condition, left (or right) participants’ hand dorsum were stimulated. In the ALIEN condition, left (or right) co-experimenter’s hand dorsum was stimulated. Participants had to rate the perceived pain on a 0-5 Likert scale (0 = no pain, 5 = maximal imaginable pain). Results showed that healthy controls and patients without delusion gave scores higher than zero only when their own hands were stimulated. On the contrary, patients with delusion gave scores higher than zero both when their own hands (left or right) were stimulated and when the co-experimenter’s left hand was stimulated. Our results show that a body part of an external individual can become, in pathological condition, so deeply embedded in one’s own somatosensory representation to have consistent effect on the subjective feeling of pain. More in general, our findings are in line with a growing number of evidence emphasizing the role of the special and unique perceptual status of body ownership in giving rise to the phenomenological experience of pain.